Whole genome sequencing identifies novel genetic mutations in patients with eczema herpeticum. Issue 8 (15th March 2021) - Bin, Lianghua; Malley, Claire; Taylor, Patricia; Preethi Boorgula, Meher; Chavan, Sameer; Daya, Michelle; Mathias, Malaika; Shankar, Gautam; Rafaels, Nicholas; Vergara, Candelaria; Potee, Joseph; Campbell, Monica; et al.
Abstract: Background: Eczema herpeticum (EH) is a rare complication of atopic dermatitis (AD) caused by disseminated herpes simplex virus (HSV) infection. The role of rare and/or deleterious genetic variants in disease etiology is largely unknown. This study aimed to identify genes that harbor damaging genetic variants associated with HSV infection in AD with a history of recurrent eczema herpeticum (ADEH+). Methods: Whole genome sequencing (WGS) was performed on 49 recurrent ADEH+ (≥3 EH episodes), 491 AD without a history of eczema herpeticum (ADEH−) and 237 non‐atopic control (NA) subjects. Variants were annotated, and a gene‐based approach (SKAT‐O) was used to identify genes harboring damaging genetic variants associated with ADEH+. Genes identified through WGS were studied for effects on HSV responses and keratinocyte differentiation. Results: Eight genes were identified in the comparison of recurrent ADEH+to ADEH−and NA subjects: SIDT2, CLEC7A, GSTZ1, TPSG1, SP110, RBBP8NL, TRIM15, and FRMD3 . Silencing SIDT2 and RBBP8NL in normal human primary keratinocytes (NHPKs) led to significantly increased HSV‐1 replication. SIDT2 ‐silenced NHPKs had decreased gene expression of IFNk and IL1b in response to HSV‐1 infection. RBBP8NL ‐silenced NHPKs had decreased gene expression of IFNk, but increased IL1b. Additionally, silencing SIDT2 and RBBP8NL also inhibited gene expression of keratinocyte differentiation markers keratin 10 (KRT10) and loricrin (LOR). Conclusion: SIDT2 and RBBP8NL participate in keratinocyte's response to HSV‐1 infection. SIDT2 and RBBP8NL also regulate expression of keratinocyte differentiation genes of KRT10 and LOR. Abstract : Whole genome sequencing was used to search genome‐wide for deleterious genetic variants that are differentially enriched in ADEH+compared to ADEH−and non‐atopic controls. A gene‐based comparison between cases and controls was used prioritize genes enriched for such variants to be followed up for functional validation. Functional validation reveals two genes: SIDT2 and RBBP8NL are involved in keratinocyte differentiation and responses against HSV‐1 infection.